Chédiak-Higashi Syndrome: A Case Report - Patne, Shashikant C. U. (Springer-Verlag, 2012)
Chédiak-Higashi syndrome (CHS) is an extremely rare autosomal recessive immunodeficiency disorder. Approximately 200 cases have been reported worldwide. To the best of our knowledge, not more than 10 cases have been reported from India. Herein we are reporting a case of CHS in one-and-half-year-old boy who presented to us in the accelerated phase of disease. Other syndromes presenting with similar clinical features have also been discussed.